The Relationship between Incorrect Body Posture in Elementary School Children on Idiopathic Scoliosis - Renni Hidayati Zein; Ayu Permata (POLTEKKES KEMENKES PONTIANAK, 2024)
Idiopathic scoliosis is a condition of spinal deformity characterized by abnormal lateral curvature. The factor that is thought to play a role in the development of idiopathic scoliosis is incorrect body posture. This research is a correlation study which aims to determine the significant relationship between incorrect body posture and the incidence of idiopathic scoliosis in elementary school children. This research approach uses a quantitative approach with a descriptive quantitative research type with a correlational model. Research data was obtained through questionnaires, documentation and measurements using a scoliometer. The population in this study were all sixth grade students at SDIT Bangkinang Elementary School, totaling 35 students. Independent variable is a sitting position using the Questionnaire on Body Awareness of Postural Habits in Young People (Q BAPHYP) measurement tool. The dependent variable is scoliosis measured using the Adam's Forward bending test. Data analysis techniques are descriptive statistical analysis and inferential statistical analysis. After analyzing the research results, it shows that incorrect body posture has a significant relationship with the incidence of idiopathic scoliosis in elementary school children as proven by the results of data analysis, p= 0.000 or p< 0.05. The conclusion of this study is that there is a significant relationship between incorrect body posture and the incidence of idiopathic scoliosis in elementary school children.